Cross-cutting concepts to transform agricultural research - Boyd, Abigail P.; Luo, Yaguang; Kustas, William P.; Fukagawa, Naomi K.; Mattoo, Autar K.; Crow, Wade T.; Pachepsky, Yakov; Kim, Moon S.; Lillehoj, Hyun S.; Van Tassell, Curtis P.; Zhang, Howard; Blomberg, Le Ann; et al. (Frontiers in Sustainable Food Systems, 2023)
Agriculture is an important link to many issues that challenge society today, including adaptation to and mitigation of climate change, food security, and communicable and non-communicable diseases in animals and humans. Transformation of agriculture and food systems has become a priority for a range of federal agencies and global organizations. It is imperative that food and agricultural researchers effectively harness the global convergence of priorities to overcome research “silos” through deep and sustained systemic change. Herein, we identify intersections in federal and global initiatives encompassing climate adaptation and mitigation; human health and nutrition; animal health and welfare; food safety and security; and equity and inclusion. Many agencies and organizations share these priorities, but efforts to address them remain uncoordinated and opportunities for collaboration untapped. Based on the interconnectedness of the identified priority areas, we present a research framework to catalyze agricultural transformation, beginning with the research enterprise. We propose that transformation in agricultural research should incorporate (1) innovation, (2) integration, (3) implementation, and (4) evaluation. This framework provides approaches for food and agricultural research to contribute to sustainable, flexible, and coordinated transformation in the agricultural sector.